Introduction to the Special Issue on Philosophy of Science and Islamic Thought - Malik, Shoaib Ahmed (Theology and science, 2023)
This is an introduction to the special issue. It provides the historical context of Islam and Science that then leads to the theme of the issue. This special issue is the proceedings of a conference at Cambridge Muslim College that was held in December 2022.